"Aid from the Indians Themselves": Native Rivalries, Spanish Precedent, and French and English Colonialism. (4th May 2019) - DeCoster, Jonathan
Abstract : Accounts of the Spanish colonial conquests circulated widely throughout Europe in the sixteenth and seventeenth centuries in their original forms, in translations, and in edited collections. Modern historians have justly criticized how this literature perpetuated a narrative of European exceptionalism and superiority, but even the most Eurocentric accounts contained within them traces of a counternarrative of Spanish dependence on Indigenous allies rather than dominance over them. Furthermore, the writings of French and English would-be colonizers show that despite their prejudices against Spain, as they scoured this literature for clues as to how to repeat Spanish successes, some recognized how political divisions amongst Native people had proven crucial for the Spaniards. This precedent convinced them to pursue a strategy of seeking out political divisions amongst Natives in the hopes of creating intercultural alliances, a dynamic that played an important role in each early French and English colony in North America.